2013
DOI: 10.1088/0957-4484/24/15/155301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal laser annealing to improve thermal contacts between multi-layer graphene and metals

Abstract: The accuracy of thermal conductivity measurements by the micro-Raman technique for suspended multi-layer graphene flakes has been shown to depend critically on the quality of the thermal contacts between the flakes and the metal electrodes used as the heat sink. The quality of the contacts can be improved by nonlocal laser annealing at increased power. The improvement of the thermal contacts to initially rough metal electrodes is attributed to local melting of the metal surface under laser heating, and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
(79 reference statements)
3
16
0
3
Order By: Relevance
“…Among them, the graphite/Ti has the highest K ⊥ , ∼120 MWm −2 K −1 , and the graphite/Au interface has the lowest K ⊥ , ∼30 MWm −2 K −1 near room temperature. Their K ⊥ of graphite/Au is consistent with the value by Norris et al and values of SLG/Au by Cai et al and FLG/Au by Ermakov et al Koh et al later measured heat flow across the Au/Ti/ n ‐LG/SiO 2 interfaces with the layer number n = 1 − 10. Their observed room‐temperature K ⊥ is ∼25 MWm −2 K −1 , which shows a very weak dependence on the layer number n and is equivalent to the total thermal conductance of Au/Ti/graphite and graphene/SiO 2 interfaces acting in series.…”
Section: Extrinsic Thermal Conductivity Of Graphenesupporting
confidence: 84%
See 1 more Smart Citation
“…Among them, the graphite/Ti has the highest K ⊥ , ∼120 MWm −2 K −1 , and the graphite/Au interface has the lowest K ⊥ , ∼30 MWm −2 K −1 near room temperature. Their K ⊥ of graphite/Au is consistent with the value by Norris et al and values of SLG/Au by Cai et al and FLG/Au by Ermakov et al Koh et al later measured heat flow across the Au/Ti/ n ‐LG/SiO 2 interfaces with the layer number n = 1 − 10. Their observed room‐temperature K ⊥ is ∼25 MWm −2 K −1 , which shows a very weak dependence on the layer number n and is equivalent to the total thermal conductance of Au/Ti/graphite and graphene/SiO 2 interfaces acting in series.…”
Section: Extrinsic Thermal Conductivity Of Graphenesupporting
confidence: 84%
“…The thermal interface conductance across graphene/graphite and other materials has been measured by using 3ω method, time‐domain thermoreflectance (TDTR) technique, and Raman‐based method, Most experimental data available to date are shown in Figure , and they are consistent with each other in general, given the variations of sample qualities and measurement techniques. Chen et al and Mak et al showed the thermal interface conductance per unit area of graphene/SiO 2 is K ⊥ ∼ 50 − 100 MWm −2 K −1 at room temperature, with no strong dependence on the FLG thickness.…”
Section: Extrinsic Thermal Conductivity Of Graphenementioning
confidence: 80%
“…Recently, we have observed 25 that MLG structures (that can be also called thin graphite nanoplatelets for thickness exceeding 10 monolayers 15 ) obtained by sonication of natural graphite demonstrate extremely high stability under heating by laser in air, with sample temperatures exceeding 1000 °C, i.e., under conditions when other graphitic materials including multi-walled carbon nanotubes (usually, more defective) are known to burn out very fast 26 27 .…”
mentioning
confidence: 99%
“…All FARMD simulations were carried out using the ReaxFF force field [3], as available in the Large-scale Atomic/Molecular Massive Parallel Simulator (LAMMPS) code [4]. In order to mimic the experimental conditions [2], our structural models consist of passivated multi-layer (6 layers) graphene, each layer with dimensions of 36x26 Å 2 (334 atoms). The multi-layer structure is placed on top of a rugous nickel substrate (size of 64x52x40 Å 3 , 5580 atoms); see Figure 2(a).…”
Section: Methodsmentioning
confidence: 99%
“…Layout of the experiment[2]. Graphene membranes are suspended over a metallic surfaces and laser beam irradiated.…”
mentioning
confidence: 99%